Gallipoli : the end of the myth - Prior, Robin (Yale University Press, 2010)
Overview: World War I's Gallipoli campaign was an ill-fated Allied attempt to shorten the war by eliminating Turkey, creating a Balkan alliance against the Central Powers, and securing a sea route to Russia. Now in paperback, this is the definitive report of this dramatic and tragic operation.